Adaptação acadêmica e relação com a evasão: identificação de indicadores - Peron, Vanessa Demarchi (2019)
The process of adapting the student to the university context is complex and involves multiple factors. Non-adaptation leads to unsatisfactory levels of academic performance, increase in repetition and university dropout rates. The evasion, in turn, generates negative impacts for the institutions (public and private) and for society. Higher education is a means of social advancement and generation of knowledge, employment and income. In addition to generating social losses, dropping out of school generates financial impacts, because each drop out represents a waste of resources, compromising the sustainability of institutions. The objective of this study was to identify if the levels of academic adaptation may indicate a tendency of university dropout. The study was conducted with students from the first period of the graduate courses at IFPR campus Foz do Iguaçu. To know the levels of university adaptation, the scale used was QVA-r (Academic Experiences Questionnaire - short version). After the application of the questionnaire, a survey of the evaded students was performed, to compare the degree of adaptability of the students who remain in the course with the dropout students. As a result, it was found that academic adaptation, mapped in the second month of school, can be predictive of dropout, allowing the institution to identify the most critical cases and develop actions to support adaptation and permanence.